Exploring A Private Islamic Primary School Teachers’ Perspectives on English as Medium of Instruction (EMI): A Phenomenological Case Study - Fanani, Roni Afero; Syahria, Nukmatus; Nurjati, Nunung (Jurnal Pendidikan Indonesia, 2025)
This phenomenological case study explores teachers' perspectives on implementing English as a Medium of Instruction (EMI) with the Cambridge curriculum in a rural Islamic primary school in Mojokerto, Indonesia. Against the backdrop of global EMI expansion and Indonesia’s push for bilingual education, the study addresses gaps in EMI research, which predominantly focuses on higher education. Through interviews and classroom observations, four key challenges emerged: teacher language proficiency, students’ low English comprehension, inadequate professional development, and teaching anxiety, rooted in rural and non-English educational backgrounds. Conversely, benefits included global competence, improved English skills, elevated school credibility, and teacher enthusiasm. Findings underscore the transformative potential of EMI in marginalized settings, alongside the need for context-specific teacher training and curriculum integration. The study advocates for longitudinal research on student outcomes and technology-enhanced solutions to address rural disparities, contributing to debates on equitable EMI implementation in religious and low-resource contexts.